CXCR4+ Sorted Adipose-Derived Stem Cells Enhance Their Functional Benefits and Improve Cardiac Function after Myocardial Infarction. (23rd August 2022) - Yuan, Zihui; Cai, Chuanqi; Qin, You; Yan, Kai; Wang, Jian
Abstract : Objective . The homing of adipose-derived stem cells (ASCs) to infarcted myocardium, which is important for improved cardiac function, has been investigated previously, but with poor efficiency. Substantial improvements in engraftments are required to optimize ASC treatment. Stromal derived factor-1 α (SDF-1 α ) is upregulated early after MI, and its endogenous receptor, chemokine receptor 4 (CXCR4), is pivotal in stem cell survival, migration, and engraftment. We examined whether CXCR4 + ASCs enhance their efficacy of migration and engraftment posttransplantation and improve heart function following myocardial infarction (MI). Methods and Results . CXCR4 + ASC subpopulations were sorted by fluorescence-activated cell sorting. CXCR4 + sorted ASCs exhibited the stronger cell viability, the faster proliferation rate, and the better migration capability in comparison with unfractionated ASCs. CXCR4 + sorted ASCs secreted a higher level of angiogenic growth factors including VEGF, HGF, and IGF-1 relative to unfractionated ASCs. Fewer apoptotic cells under oxygen-glucose deprivation were detected in CXCR4 + sorted ASCs than in unfractionated ASCs. Osteogenic and angiogenic differentiation were more pronounced in CXCR4 + sorted ASCs than in unfractionated ASCs. At 3 days after acute MI, rats were randomly allocated to receive intramyocardial injection of cell culture medium, CXCR4 + sorted ASCs, and unfractionated ASCs. Left ventricular function was assessed echocardiographically 4 weeks thereafter. Explanted hearts were then processed for the immunofluorescence detection of survived cells, quantification of angiogenesis, and cell engraftment. CXCR4 + sorted ASCs more obviously engrafted into infarcted myocardium, more markedly inhibited collagen remodeling, and more effectively improved heart function and promoted capillary formation than did unfractionated ASCs. Conclusion . CXCR4 + sorted ASCs are superior to unfractionated ASCs due to better viability, faster proliferation, more cytokine secretion, and stronger migration. CXCR4 + sorted ASCs provide better curative benefits on MI than do unfractionated ASCs and can be efficiently harvested and purified from adipose tissue, they may serve as a promising candidate for MI.